ANALISA HASIL BELAJAR MENGGUNAKAN MODEL PjBL PADA MATERI KONSEP MEKANIKA ENERGI - Pramitasari, Retno Eka; Wati, Dian Anisa Rokhmah; Basuki, Basuki; Hadi, Fajar Satriya; Ummah, Imamatul; Kholis, Nur (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
An excellent generation with noble character and knowledge is the goal of implementing education. The implementation of appropriate learning can provide good learning outcomes. The PjBL learning model is one of the cooperative learning models that requires students to work together in completing a predetermined project. The purpose of this study was to analyze student learning outcomes before and after the PjBL learning process and project-based learning outcomes. This study uses a one group pre-test post-test design, a sample of 15 students using the PjBL learning model as the treatment applied and analyzing the learning outcomes obtained by students during the learning process. This study concludes that through the implementation of the PjBL learning model, it provides differences in learning outcomes before and after the learning process is held on the material of energy mechanics concepts in the thermodynamics course with a value 0f 0,000. In addition, based on the research results obtained, the results of project-based learning produce good average values with an average value reaching 90% of student were able to complete the tasks thad had been given